Regulation of sexually dimorphic placental adaptation in LPS exposure-induced intrauterine growth restriction - Da Som Jeong; Ji-Yeon Lee; Myoung Hee Kim; Ji Hoon Oh (BMC, 2023)
Abstract Background Sexual dimorphism in placental physiology affects the functionality of placental adaptation during adverse pregnancy. Defects of placental function compromise fetal programming, affecting the offspring's adult life. However, studies focusing on the relationship between sex-specific placental adaptation and consequent fetal maldevelopment under sub-optimal uterus milieu are still elusive. Methods Here, we investigated the effects of maternal lipopolysaccharide (LPS) exposure between placental sex. Pregnant ICR mice received intraperitoneal injection of phosphate-buffered saline or 100, 200, and 400 µg/kg LPS on the gestational day (GD) 15.5. To determine whether prenatal maternal LPS exposure resulted in complicated pregnancy outcomes, survival rate of embryos was calculated and the growth of embryos and placentas was examined. To elucidate global transcriptomic changes occurring in the placenta, total RNA-sequencing (RNA-seq) was performed in female and male placentas. Results LPS administration induced placental inflammation in both sexes at GD 17.5. Prenatal infection resulted in growth retardation in both sexes of embryos, and especially more prevalently in male. Impaired placental development was observed in a sex-specific manner. LPS 400 µg/kg reduced the percentage area of the labyrinth in females and junctional zone in males, respectively. RNA-sequencing revealed widespread sexually dimorphic transcriptional changes in placenta. In particular, representative changes were involved in biological processes such as trophoblast differentiation, nutrient/ion transporter, pregnancy, and immune system. Conclusions Our results present the sexually dimorphic responses of placental physiology in intrauterine growth restriction model and provide tentative relationship further to be elucidated between sex-biased placental functional change and long-term effects on the offspring's later life.